Development of Masking Learning Module for Vocational High School Automotive Body Engineering Expertise Competency - Rabiman Rabiman; Muhammad Ali Azhar (Universitas Sultan Ageng Tirtayasa, 2024)
The purpose of this research is to produce a learning module that is feasible for learning to carry out masking on unrepaired vehicle body parts. The data collection technique in this study is using a student response questionnaire using a Likert scale. This type of research is research and development (R&D) using the 4-D research model. The subjects of this research were XI TBR class students at SMK Kristen 5 Klaten, totaling 30 students. Data analysis using percentage techniques. The results showed that based on the results of the assessment by material experts, media experts, and trials to students, the learning module developed was feasible for use in learning. The assessment of the feasibility of learning modules by material experts received a score of 75% with feasible criteria, the assessment of media experts received a score of 75% with feasible criteria and the results of trials to students as users received a score of 86% with a very feasible category. Therefore, this module can be used in learning to carry out masking on unrepaired vehicle body parts for students of Light Vehicle Body Engineering.